Gestational trophoblastic disease in Switzerland: retrospective study of the impact of a regional reference centre (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY The European Society of Medical Oncology (ESMO) recommends that countries should have reference centres to provide adequate diagnosis and treatment of gestational trophoblastic disease. A trophoblastic disease centre in the French-speaking part of Switzerland was inaugurated in 2009. The objectives of this study were to report the activity of the centre during the last 10 years and analyse gestational trophoblastic disease outcomes. METHODS This was a retrospective study with data collected from all cases of gestational trophoblastic disease referred to the centre from 2009 to 2018. All histological specimens as well as data for treatment and follow-up of gestational trophoblastic disease and neoplasia were reviewed. Clinical features, including age, prognostic score and International Federation of Gynecology and Obstetrics (FIGO) stages (in the case of gestational trophoblastic neoplasia), human chorionic gonadotropin (hCG) follow-up, treatment and outcome were reported. RESULTS The centre registered 354 patients, and these patients presented 156 cases of partial hydatidiform moles, 163 cases of complete hydatidiform moles and 14 cases of gestational trophoblastic neoplasia. During follow-up, 35 gestational trophoblastic neoplasms were diagnosed after hCG persistence. After pathology review, the overall agreement rates between our centre and a participating provider hospital was 82%. Methotrexate was the first line of single-agent chemotherapy for most patients, with resistance rates of 23%. Multi-agent chemotherapy was used as first-line treatment for five patients. None of the patients followed up by the centre died from gestational trophoblastic disease. CONCLUSIONS This study reflects the activity of the Swiss trophoblastic disease centre from the French-speaking part of Switzerland created in 2009, and its role as local and national reference centre, in terms of global health, for women with gestational trophoblastic disease.